COUNTERFEIT GOODS IN THE MARKETPLACE ON THE EXAMPLE OF WILDBERRIES: PROBLEM STATEMENT - A. V. Sal’nikova; Yu. A. Kudimova (Вестник университета, 2021)
The article analyses the distribution of counterfeit products through marketplaces in Russia in the context of the rapid growth of e-commerce, as well as the COVID-19 pandemic. Based on the analysis of statistical data of reports and reports of companies and organizations specializing in research of the counterfeit market in Russia, the paper concludes that marketplaces are one of the channels for the distribution of counterfeit goods. The consequences of selling counterfeit goods online have a negative impact on the state, which does not receive tax revenues to the budget, rights holders who lose their profits and reputation, as well as on consumers in the form of harm to health and threat to life. The study of the work of one of the popular marketplaces Wildberries allows us to speak about the lack of interest of the marketplace as an online trading platform in monitoring sellers (suppliers) of goods for violation of intellectual property rights. The authors of the article made a number of proposals to improve measures to counter the appearance and spread of counterfeit goods through marketplaces. The paper determines that the fight against counterfeiting should be carried out in a complex and only with the interested participation of the state, copyright holders, buyers and marketplaces.